Moisture-induced strength degradation of aggregate-asphalt mastic bonds - Apeagyei, Alex K.; Grenfell, James; Airey, Gordon (Taylor & Francis, 2014)
A common manifestation of moisture-induced damage in asphalt mixtures is the loss of adhesion at the aggregate–asphalt mastic interface and/or cohesion within the bulk mastic. This paper investigates the effects of moisture on the aggregate–mastic interfacial adhesive strength as well as the bulk mastic cohesive strength. Physical adsorption concepts were used to characterise the thermodynamic work of adhesion and debonding of the aggregate–mastic bonds using dynamic vapour sorption and contact angle measurements. Moisture diffusion in the aggregate substrates and in the bulk mastics was determined using gravimetric techniques. Mineral composition of the aggregates was characterised by a technique based on the combination of a scanning electron microscope and multiple energy dispersive X-ray detectors. Aggregate–mastic bond strength was determined using moisture-conditioned butt-jointed tensile test specimens, while mastic cohesive strength was determined using dog bone-shaped tensile specimens. Aggregate–mastic bonds comprising granite mastics performed worse in terms of moisture resistance than limestone mastic bonds. The effect of moisture on the aggregate–mastic interfacial bond appears to be more detrimental than the effect of moisture on the bulk mastic.